The Influence of Promotion, Product Quality, and Price Perception on Purchasing Decisions on Converse Shoes with Brand Image as an Intervening Variable (The study focuses on the use of Converse shoes by college students in Semarang City): Analysis of the Influence of Promotion, Product Quality, and Price Perception on Purchasing Decisions on Converse Shoes with Brand Image as an Intervening Variable (The study focuses on the use of Converse shoes by college students in Semarang City) - Anggraeni, Puspita Septi; Heri Prabowo; Henry Goeltom (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research examines the decision to purchase Converse shoe products among female students in the city of Semarang. This research aims to determine the influence of promotions, product quality, and price perceptions on purchasing decisions for Converse shoe products. This research method is a quantitative research method. The population in this study were all students and female students in the city of Semarang, while the sample in this study was 96 people. Data collection techniques were used by distributing questionnaires online via Google Form. Data analysis in this research used the SmartPLS programme version 3.2.9. The data analysis technique used is the structural equation modelling (SEM) equation model. The results of the discussion analysis show that the promotion variable has no effect on brand image, product quality has an effect on brand image, price perception has an effect on brand image, promotion has no effect on purchasing decisions, product quality has no effect on purchasing decisions, price perception has an effect on purchasing decisions, brand image influence on purchasing decisions, promotions have no influence on purchasing decisions among students and female students using Converse shoes in Semarang City which are mediated by brand image, product quality does not influence purchasing decisions among students and female students using Converse shoes in Semarang City which are mediated by brand image, price perception influences purchasing decisions among students who use Converse shoes in Semarang City, which is mediated by brand image.